Debating self-knowledge - Brueckner, Anthony, 1953-; Ebbs, Gary. (New York : Cambridge University Press, 2012)
'Language users ordinarily suppose that they know what thoughts their own utterances express. We can call this supposed knowledge minimal self-knowledge. But what does it come to? And do we actually have it? Anti-individualism implies that the thoughts which a person's utterances express are partly determined by facts about their social and physical environments. If anti-individualism is true, then there are some apparently coherent sceptical hypotheses that conflict with our supposition that we have minimal self-knowledge. In this book, Anthony Brueckner and Gary Ebbs debate how to characterize this problem and develop opposing views of what it shows. Their discussion is the only sustained, in-depth debate about anti-individualism, scepticism and knowledge of one's own thoughts, and will interest both scholars and graduate students in philosophy of language, philosophy of mind and epistemology'--
Introduction -- 1. Brains in a vat / Anthony Brueckner -- 2. Scepticism, objectivity, and brains in vats / Gary Ebbs -- 3. Ebbs on scepticism, objectivity, and brains in vats / Anthony Brueckner -- 4. The dialectical context of Putnam's argument that we are not brains in vats / Gary Ebbs -- 5. Trying to get outside your own skin / Anthony Brueckner -- 6. Can we take our words at face value? / Gary Ebbs -- 7. Is scepticism about self-knowledge incoherent? / Anthony Brueckner -- 8. Is scepticism about self-knowledge coherent? / Gary Ebbs -- 9. The coherence of scepticism about self-knowledge / Anthony Brueckner -- 10. Why scepticism about self-knowledge is self-undermining / Gary Ebbs -- 11. Scepticism about self-knowledge redux / Anthony Brueckner -- 12. Self-knowledge in doubt / Gary Ebbs -- 13. Looking back / Anthony Brueckner.
Includes bibliographical references (p. 227-230) and index.
Keywords: Self-knowledge, Theory of; Individualism; Skepticism; Language and languages -- Philosophy